2009
DOI: 10.1253/circj.cj-09-0710
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-Like Proteins Potential Therapeutic Targets for Metabolic Syndrome and Cardiovascular Disease

Abstract: Recent major increases in obesity and related metabolic diseases (known as the metabolic syndrome (MetS)) because of sedentary lifestyles and overnutrition in developed and developing countries, are an exploding medical and social problem. These conditions are associated with increased risk of cardiovascular disease (CVD), the leading cause of death. Thus, it is necessary to understand the molecular basis underlying MetS and develop effective preventive and therapeutic approaches against CVD. To date, 7 angiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 62 publications
3
41
0
Order By: Relevance
“…20, 21, 22 We found that Angptl2 levels tended to decrease immediately in subjects showing 2% or more weight reduction and continued until 3 months after the intervention. Angptl2 gradually decreased with increased weight reduction, and those decreases in the 6% or more weight reduction group were significant compared with the unchanged control group, indicative of an early effect of weight reduction on improved metabolism.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…20, 21, 22 We found that Angptl2 levels tended to decrease immediately in subjects showing 2% or more weight reduction and continued until 3 months after the intervention. Angptl2 gradually decreased with increased weight reduction, and those decreases in the 6% or more weight reduction group were significant compared with the unchanged control group, indicative of an early effect of weight reduction on improved metabolism.…”
Section: Discussionmentioning
confidence: 60%
“…20, 21, 22 We observed accumulation of fat in the liver and skeletal muscle was mild in Angptl2 knockout mice compared with wild-type mice, and Angptl2 deletion ameliorated adipose tissue inflammation. 20 We also observed significant decreases in circulating Angptl2 concentrations in obese diabetic men following treatment with the PPARγ agonist pioglitazone, and the percent decrease in Angptl2 levels was positively correlated with the percent decreases in visceral fat area.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…178 Angiopoietins and their receptors, as well as the apelin-APJ signaling pathway, can also be promising targets for anti-angiogenesis of WAT. 179, 180 Established vasculature of WAT could be targeted as well since data from animal studies showed that a cytotoxic peptide fused to the ligand of prohibitin, a receptor specifically located to WAT endothelium, resulted in rapid obesity reversal upon daily subcutaneous injection; 181 similar results were obtained from a rat model of obesity. 182 Future translational studies will be necessary to validate this approach.…”
Section: Targeting Human Adipose Tissue For Treating Obesity-related mentioning
confidence: 91%
“…Angiopoietin-like (ANGPTL) molecules are a family of glycoproteins which resemble angiopoietins structurally [82] but fail to bind the angiopoietin receptors Tie1 and Tie2 [8385]. Despite these, some of the members in this family are potent regulators of angiogenesis [86, 87] and function as mediators in the induction of inflammation and regulation of lipid and glucose metabolism [8890].…”
Section: Resultsmentioning
confidence: 99%